The Role of Media in The National Development Process of Timor-Leste - Fransisco de Deus Maia; Santino Barros; Juvenal da Costa (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The topic of this jure is "the Role of Media in the National Development Process of Timor-Leste," the research method used is descriptive qualitative. Analysis based on phenomena that occur in the country through social media, direct observation and bibliography studies to analyze and compare the reality in order to draw an appropriate conclusion. It is therefore recommended that the relevant entities, especially the Government, so that the formulation of this program is accumulative, the effective use of less communication and the regulation of less communication so that all communication takes place in a positive channel. So social media is not an obstacle, but social media can be an important channel or bridge to contribute to national development. On the other hand, it is also recommended that the Government consider how to improve the lack of communication in Timor-Leste so that all communities use the lack of all communication with responsibility so that it does not have a negative impact on the future of the Nation in order to help the national development process.